Function of B-Cell CLL/Lymphoma 11B in Glial Progenitor Proliferation and Oligodendrocyte Maturation - Wang, Chih-Yen; Sun, Yuan-Ting; Fang, Kuan-Min; Ho, Chia-Hsin; Yang, Chung-Shi; Tzeng, Shun-Fen (Frontiers in Molecular Neuroscience, 2018)
B-cell CLL/lymphoma 11B (Bcl11b) – a C2H2 zinc finger transcriptional factor – is known to regulate neuronal differentiation and function in the development of the central nervous system (CNS). Although its expression is reduced during oligodendrocyte (OLG) differentiation, its biological role in OLGs remains unknown. In this study, we found that the downregulation of Bcl11b gene expression in glial progenitor cells (GPCs) by lentivirus-mediated gene knockdown (KD) causes a reduction in cell proliferation with inhibited expression of stemness-related genes, while increasing the expression of cell cyclin regulator p21. In contrast, OLG specific transcription factors (Olig1) and OLG cell markers, including myelin proteolipid protein (PLP) and myelin oligodendrocyte glycoprotein (MOG), were upregulated in Bcl11b-KD GPCs. Chromatin immunoprecipitation (ChIP) analysis indicated that Bcl11b bound to the promoters of Olig1 and PLP, suggesting that Bcl11b could act as a repressor for Olig1 and PLP, similar to its action on p21. An increase in the number of GC+- or PLP+- OLGs derived from Bcl11b-KD GPCs or OLG precursor cells was also observed. Moreover, myelin basic protein (MBP) expression in OLGs derived from Bcl11b-KD GPCs was enhanced in hippocampal neuron co-cultures and in cerebellar brain-slice cultures. The in vivo study using a lysolecithin-induced demyelinating animal model also indicated that larger amounts of MBP+-OLGs and PLP+-OLGs derived from implanted Bcl11b-KD GPCs were present at the lesioned site of the white matter than in the scramble group. Taken together, our results provide insight into the functional role of Bcl11b in the negative regulation of GPC differentiation through the repression of OLG differentiation-associated genes.